Revisiting the placental bed: a syndrome approach - Sagayaraj, Benjamin M.; Sharma, Nidhi; D. V., Lal (International Journal of Contemporary Pediatrics, 2016)
Background: The apt way to reduce Neonatal mortality is to identify the antenatal factors, which ascertain the uterine milieu and nutrient bioavailability. Hence this study was conducted to outline the relation between preeclampsia, Abruption, prematurity and resultant perinatal mortality and morbidity in a tertiary feto maternal care centre. Methods: This prospective study was carried out on 1800 deliveries in the Department of Obstetrics and Gynecology at Saveetha Medical College and hospital, Chennai, India between 1 October 2012 and 30 September 2013. Results: During the study period, 100 (5.55%) pregnancies resulted in Low birth weight neonates out of total 1800 pregnancies. There were 70 diagnosed patients of Pregnancy induced Hypertension by International Society for the Study of Hypertension in Pregnancy criteria. There were no intrauterine deaths. There were 6 cases of grade 1 abruption. Out of 100 low birth weight infants, 46 were preterm births. There were 54 cases of Intrauterine Growth retardation. Out of 100 low birth babies (<2000 gms) 93 survived beyond four weeks of life. Conclusions: The concept of junctional zone myometrium is not new. The term “Placental bed” was coined in 1958 for the modified endometrium and junctional zone myometrium of pregnancy. The lack of physiological transformation of spiral arteries at this feto maternal interphase has been postulated in the pathogenesis of preeclampsia, intrauterine growth retardation, spontaneous abortion, placental abruption and preterm labour. The damage of fetal tertiary stem villus from the jetting blood in the intervillous space could have led to preterm births, intrauterine growth retardation and neonatal mortality in our patients.